The agenda of climate change and sustainable development in Paris and New York forum: history of two cities (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The agendas for Climate Change and for Sustainable Development launched in Paris and New York in 2015 set a fundamental milestone in the efforts that countries, international institutions, civil society and individual people endeavor to make in order to build a global sustainable equilibrium which balances the economic, social and environmental dimensions, which does not compromise the well-being of future generations while pursuing a just, fair and safe space for humanity in the coming decades. Both agendas, as well as both issues, are complexly interrelated and require a coordinated effort towards action and innovation to achieve their multiple objectives.
Keywords: Climate Change; mitigation; adaptation; Paris Agreement; COP21; Sustainable Development Goals; Post-2015 Agenda; universal access; energy; innovation